TASK-1 potassium channel is not critically involved in mediating hypoxic pulmonary vasoconstriction of murine intra-pulmonary arteries. - Ghulam Murtaza; Petra Mermer; Anna Goldenberg; Uwe Pfeil; Renate Paddenberg; Nobert Weissmann; Guenter Lochnit; Wolfgang Kummer (PLoS ONE, 2017)
The two-pore domain potassium channel KCNK3 (TASK-1) is expressed in rat and human pulmonary artery smooth muscle cells. There, it is associated with hypoxia-induced signalling, and its dysfunction is linked to pathogenesis of human pulmonary hypertension. We here aimed to determine its role in hypoxic pulmonary vasoconstriction (HPV) in the mouse, and hence the suitability of this model for further mechanistic investigations, using appropriate inhibitors and TASK-1 knockout (KO) mice. RT-PCR revealed expression of TASK-1 mRNA in murine lungs and pre-acinar pulmonary arteries. Protein localization by immunohistochemistry and western blot was unreliable since all antibodies produced labelling also in TASK-1 KO organs/tissues. HPV was investigated by videomorphometric analysis of intra- (inner diameter: 25-40 μm) and pre-acinar pulmonary arteries (inner diameter: 41-60 μm). HPV persisted in TASK-1 KO intra-acinar arteries. Pre-acinar arteries developed initial HPV, but the response faded earlier (after 30 min) in KO vessels. This HPV pattern was grossly mimicked by the TASK-1 inhibitor anandamide in wild-type vessels. Hypoxia-provoked rise in pulmonary arterial pressure (PAP) in isolated ventilated lungs was affected neither by TASK-1 gene deficiency nor by the TASK-1 inhibitor A293. TASK-1 is dispensable for initiating HPV of murine intra-pulmonary arteries, but participates in sustained HPV specifically in pre-acinar arteries. This does not translate into abnormal rise in PAP. While there is compelling evidence that TASK-1 is involved in the pathogenesis of pulmonary arterial hypertension in humans, the mouse does not appear to serve as a suitable model to study the underlying molecular mechanisms.